A Web-Based Chatbot with Advanced Voice Control and Document Interaction Using Flask and JavaScript - Maidamshetti, Ashwini (International journal for research in applied science and engineering technology, 2025)
Chatbots in the last few years have been the subject of growing interest as smart conversational agents for human– computer interaction in various applications. Most current systems, however, have limitations like insufficient flexible voice control, limited document support, and minimal user-friendly capabilities. To overcome these drawbacks, this paper introduces a web-based chatbot system designed using Flask as the backend and JavaScript as the frontend. The system incorporates cuttingedge features like dark mode for user ease, text-to-speech with voice toggle control, selective text reading, microphone-based speech input, and document upload (PDF, DOCX, TXT) for content-based question answering. The backend utilizes the OpenRouter API to provide accurate responses, while the frontend offers an interactive and accessible interface. Experimental evaluation and user feedback emphasize that the suggested system provides greater usability, flexibility, and engagement over traditional chatbots. This research shows the possibility of integrating multi-modal capabilities with lightweight web technologies to enhance user experience in conversational AI systems.